2019
DOI: 10.1037/bne0000294
|View full text |Cite
|
Sign up to set email alerts
|

Inborn vs. acquired anxiety in cross-breeding and cross-fostering HAB/LAB mice bred for extremes in anxiety-related behavior.

Abstract: This study focused on genetically determined versus acquired factors in shaping anxiety-related behavior by combining cross-breeding and cross-fostering approaches. Via cross-breeding of HAB (high anxiety-related behavior) female and LAB (low anxiety-related behavior) male mice, we obtained F1 hybrids with intermediate anxiety levels carrying genetic characteristics of both parental lines. Pups were raised either by their biological HAB (noncross-fostered control) or foster LAB (cross-fostered) mothers. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We previously reported that wildtype (Gad1 +/+ ) mice born from GAD67 haplodeficient (Gad1 GFP/+ ) mothers exhibited the vulnerability to stress at the adult age [42]. In addition, it has been reported that the anxious state in mother mice affects behavioral phenotypes in their pups at the adult age [43]. Second, we used wild-type (Gad1 +/+ ) mice as the control, but Fujihara et al [19] used Gad1 flox/+ mice as the control.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that wildtype (Gad1 +/+ ) mice born from GAD67 haplodeficient (Gad1 GFP/+ ) mothers exhibited the vulnerability to stress at the adult age [42]. In addition, it has been reported that the anxious state in mother mice affects behavioral phenotypes in their pups at the adult age [43]. Second, we used wild-type (Gad1 +/+ ) mice as the control, but Fujihara et al [19] used Gad1 flox/+ mice as the control.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several rat and mouse models based on the selective bidirectional breeding of animals according to their performance in unconditioned anxiety tests were established [7][8][9][10]. Selective breeding models have allowed the investigation of the genetic factors that contribute to the development and expression of trait anxiety.…”
Section: In Practice Our Paradigms Are Constrained By the Way The Org...mentioning
confidence: 99%
“…To this end, several rat and mouse models based on the selective bi-directional breeding of animals according to their performance in unconditioned anxiety tests were established [7][8][9][10]. Selective breeding models have allowed the investigation of the genetic factors that contribute to the development and expression of trait anxiety.…”
Section: Introductionmentioning
confidence: 99%